2003
DOI: 10.1152/ajpregu.00733.2002
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of sympathetic efferents but not capsaicin-sensitive afferents in nociceptin-mediated dual control of rat synovial blood flow

Abstract: This study set out to examine the vasomotor effects of the opioid-like peptide nociceptin on knee joint capsular blood flow in urethane-anaesthetized rats. Topical application of nociceptin (10(-15)-10(-8) mol) caused a progressive fall in joint perfusion that was significantly inhibited by the specific nociceptin receptor antagonist [Phe(1)-(CH(2)-NH)-Gly(2)] Nociceptin(1-13)-NH(2) as well as the nonspecific opioid antagonist naloxone. To test whether this constrictor response was sympathetically mediated, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It should be noted that the local administration of VIP and VIP 6–28 had no effect on systemic blood pressure (Table 1), confirming that all vasomotor changes were localised to the joint and not influenced by centrally mediated baroreflex events. Previously, we have shown that the vehicle (0.9% NaCl, 37°C) alone has no vasoactive effects when administered to the exposed knee joint (Barin & McDougall, 2003; McDougall, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the local administration of VIP and VIP 6–28 had no effect on systemic blood pressure (Table 1), confirming that all vasomotor changes were localised to the joint and not influenced by centrally mediated baroreflex events. Previously, we have shown that the vehicle (0.9% NaCl, 37°C) alone has no vasoactive effects when administered to the exposed knee joint (Barin & McDougall, 2003; McDougall, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…A considerable amount of evidence suggests that the peripheral nervous system is involved in the development and progression of joint inflammation (Levine et al ., 1985a; 1986). Inflammatory neuropeptides such as substance P and calcitonin gene‐related peptide cause vasodilatation in joints (Levine et al ., 1984; Lam & Ferrell, 1989; Cambridge & Brain, 1992; McDougall et al ., 1995; McMurdo et al ., 1997), while opioid peptides such as endomorphin‐1 and nociceptin induce marked synovial hypoaemia (Barin & McDougall, 2003; McDougall, 2003; McDougall et al ., 2004). Although it is known that the autonomic nervous system contributes to the development and severity of arthritis (Levine et al ., 1986), the identification and mode of action of specific mediators involved in this process are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine, which acts via the -opioid receptor, has been shown to ameliorate the clinical signs of experimentally induced arthritis (20,33), whereas ␦-and -opioid agonists are also capable of reducing the morphological and pathophysiological changes associated with joint inflammation (4,10,29,34,35). The precise role of the ORL-1 receptor ligand nociceptin in joint inflammation is less clear as the peptide has been found to produce dual vasomotor effects in rat synovium (24). Although the opioid family appears to be promising therapeutic targets for the treatment of inflammatory joint disease, chronic opioid use is also renowned for generating harmful side effects as well as being associated with drug tolerance and possible addiction.…”
mentioning
confidence: 99%
“…The inhibitors tested were the NOP receptor antagonist [Phe 1 ‐(CH 2 ‐NH)‐Gly 2 ]‐Nociceptin(1–13)‐NH 2 (Noci 1–13 ; 10 −9 mol), the NK 1 receptor antagonist [ D ‐Arg1, D ‐Phe5, D ‐Trp7,9,Leu11]‐Substance P ([ D ‐Arg]‐SP; 10 −12 mol), the VPAC receptor antagonist VIP 6–28 (10 −9 mol) and the CGRP receptor antagonist CGRP 8–37 (10 −9 mol). With the exception of [ D ‐Arg]‐SP, these antagonists have previously been shown to block their respective receptors at the specified doses in the rat knee joint (McMurdo et al ., 1997; McDougall, 2003; McDougall & Barin, 2005). NK 1 receptor blockade with [ D ‐Arg]‐SP was confirmed in the rat knee by its ability to antagonise SP‐mediated vasodilatation (see Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro pharmacological studies on precontracted arterial rings demonstrated a vasorelaxant effect of N/OFQ (Gumusel et al ., 1997; Champion et al ., 1998b) indicating a peripheral role for the peptide in counteracting vasomotor tone. Conversely, in vivo blood flow experiments carried out on joints revealed a vasoconstrictor effect of N/OFQ, which proved to be sympathetically mediated (McDougall, 2003).…”
Section: Introductionmentioning
confidence: 99%